Pendekatan HAM dalam Reformasi Pelindungan Pekerja Migran Indonesia - Syarafina Fildzah; Silssy Wahyu Indraswari; Anang Dony Irawan (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study discusses the relevance of human rights in the protection system for Indonesian migrant workers. It addresses two main issues the implementation of human rights principles in regulations concerning the protection of Indonesian migrant workers, and bilateral agreements between Indonesia and destination countries in safeguarding the rights of migrant workers. The research employs a normative legal method with a statutory approach and analysis of international human rights instruments as well as national regulations. The findings reveal that although Indonesia has ratified various human rights instruments, their implementation remains weak, particularly in terms of legal protection and access to justice. Therefore, it is necessary to strengthen regulations and establish human rights-based monitoring mechanisms to ensure the effective and sustainable protection of Indonesian migrant workers’ rights.